Formalizing Object-Oriented Design Metrics upon the UML Meta-Model - Baroni, Aline Lúcia; Brito e Abreu, Fernando (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2002: Anais do XVI Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2002.23943, 2002)
This paper discusses the formalization effort of object-oriented design metrics definitions and presents some concrete examples, developed upon the UML meta-model. The Object Constraint Language (OCL), a part of the Unified Modeling Language (UML) standard, is used in the formalization. The combination of the UML meta-model and OCL allows unambiguous metrics definition, which in turn helps increasing tool support for object-oriented metrics extraction. This formalization renders possible the comparisons among different sets of metrics, as well as it may be used to establish a common vocabulary among different stakeholders. As consequence, the precision of the metrics collection increases, contributing to the overall quality of the Software Engineering process.